1969
DOI: 10.2135/cropsci1969.0011183x000900040007x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Persistence and Depletion in Buried Seed Populations. I. A Model for Analysis of Parameters of Buried Seed Persistence and Depletion.1

Abstract: A model describing the parameters of persistence and depletion within buried seed populations is presented. This model provides a conceptual framework for problems involving buried seed persistence and depletion which are often encountered in weed control and crop seed certification. Them model may also find use in studies where the ecology, physiology and genetics of buried seed persistence and depletion are being evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0
1

Year Published

1972
1972
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…The models generally include a persistent component composed of seeds under different types of dormancy, and a nonpersistent component composed of germinating seeds and seeds losing viability prior to germination. The goal of predictve seed bank models is to understand the phenomena of persistence and depletion among seed bank populations and then use this information to develop strategies to destroy buried seed populations through germination stimulation or by direct action of toxicants (Schafer and Chilcote 1969). Information for input into the models is derived from seed burial and seedling pattern studies carefully designed to account for depletion through germination and mortality.…”
mentioning
confidence: 99%
“…The models generally include a persistent component composed of seeds under different types of dormancy, and a nonpersistent component composed of germinating seeds and seeds losing viability prior to germination. The goal of predictve seed bank models is to understand the phenomena of persistence and depletion among seed bank populations and then use this information to develop strategies to destroy buried seed populations through germination stimulation or by direct action of toxicants (Schafer and Chilcote 1969). Information for input into the models is derived from seed burial and seedling pattern studies carefully designed to account for depletion through germination and mortality.…”
mentioning
confidence: 99%
“…Schafer and Chilcote (1969) proposed a seed bank dynamics model on the basis of the summation of persistent seeds prevented from germination by endogenous (dormancy) and exogenous (quiescence) factors, and seeds that germinate or die as a result of predation or aging. Granivores have significant impacts on seed banks in arid and semi-arid habitats.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pathogens (fungi) can destroy a significant portion of seed banks (35%) in semi-arid shrubland and interact with harvesting ants that selectively predate non-infected seeds (Crist and Friese, 1993). Roberts (1972) and Baskin and Baskin (1998) incorporated failure of seedling emergence into the seed bank dynamics model of Schafer and Chilcote (1969). Meyer (1986) stressed that the unusual physical rather than chemical soil properties was the main reason for specialised vegetation developing in arid and semi-arid gypsum habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roberts (1970) and Roberts & Feast (1972) showed that weed seed dissipated more rapidly from cultivated than untilled soil and this influences generalizations made of shattercane longevity in buried seed studies versus cultivated field situations. A model describing the parameters of persistence and depletion within buried seed populations was presented by Schafer & Chilcote (1969). Additional information is needed on long-term persistence of shattercane seed across soil and climatic regimes.…”
Section: Introductionmentioning
confidence: 99%